Status of diagnosis and therapy of abdominal aortic aneurysms - Lin, Jinping; Chen, Shuwei; Yao, Yuanyuan; Yan, Min (Frontiers in Cardiovascular Medicine, 2023)
Abdominal aortic aneurysms (AAAs) are characterized by localized dilation of the abdominal aorta. They are associated with several serious consequences, including compression of adjacent abdominal organs, pain, treatment-related financial expenditure. The main complication of AAA is aortic rupture, which is responsible for about 200,000 deaths per year worldwide. An increasing number of researchers are dedicating their efforts to study AAA, resulting in significant progress in this field. Despite the commendable progress made thus far, it remains a lack of established methods to effectively decelerate the dilation of aneurysms. Therefore, further studies are imperative to expand our understanding and enhance our knowledge concerning AAAs. Although numerous factors are known to be associated with the occurrence and progression of AAA, the exact pathway of development remains unclear. While asymptomatic at most times, AAA features a highly unpredictable disease course, which could culminate in the highly deadly rupture of the aneurysmal aorta. Current guidelines recommend watchful waiting and lifestyle adjustment for smaller, slow-growing aneurysms, while elective/prophylactic surgical repairs including open repair and endovascular aneurysm repair are recommended for larger aneurysms that have grown beyond certain thresholds (55mm for males and 50mm for females). The latter is a minimally invasive procedure and is widely believed suited for patients with a poor general condition, however, several concerns have recently been raised regarding the postoperative complications and possible loss of associated survival benefits on it. In this review, we aimed to highlight the current status of diagnosis and treatment of AAA by combining the findings on literatures review.